Pengaturan Santunan Asuransi Kecelakaan Penumpang dan Driver Go-Ride yang Diberikan Oleh PT Gojek - Bhakti, Guntur Satrio; Widiastuti, Widiastuti; Setiodjati, Josef Purwadi (Faculty of Law, Universitas Slamet Riyadi, 2022)
Indonesia is now entering the digital era and is developing not only in information technology but also in the field of transportation. People can now order motorcycle public transport (Go- Ride) only through the application. Go-Ride is one of the services provided by Gojek, whose mission is to carry passengers. High interest in the use of Go-Ride can cause traffic accidents. The purpose of this investigation is to find laws and regulations regarding insurance for public transport passengers and to determine regulations regarding the fulfillment of insurance claims due to accidents between passengers and Go-Ride drivers. The type of study used by the author is normative study. The nature of this study is descriptive and analytical. The data sources used in this study are primary and secondary data sources. In the data analysis method of this study, the author uses qualitative data analysis using an interactive model. The results of this study explain the regulations that Gojek used as a reference for implementing insurance. The regulation in question is Road Traffic and Transportation Law No. 22 of 2009, which requires all carriers to be held responsible in the event of a passenger accident, with Go-Ride passengers and drivers in an accident. Explains the mechanism of providing insurance coverage in the event of an accident. There are two types of highways and passenger insurance is Basic penumpang Go¬-Ride dan Perjalanan Aman+.